(untitled) (International Journal of Engineering and Computer Science, 2015)
The requirements of information security within an organization have undergone tremendous changes. Before the widespread use of data processing equipment, the security of sensitive documents depends on filing cabinets with a combination lock for storing paper-based files or documents. However the scenario has change with the introduction of computer in handling businesses in organizations. At the same time, advances in networking and communication technology bring the business organizations worldwide working together as one entity. Due to the impact of this globalization, vast amount of various digital documents such as texts, images, videos, or audio travels from one destination to another via the network line. However some of these documents might be sensitive and confidential and therefore need to be protected. Image Encryption is the process of encoding messages in such a way that eavesdroppers or hackers cannot read it, however that authorized parties. With the huge growth of computer networks and the latest advances in digital technologies, a huge amount of digital data is being exchanged over various types of networks. It is often true that a large part of this information is either confidential or private.